IMPLEMENTATION OF THE ASSESSMENT OF THE PANCASILA AND RAHMATAN LIL ALAMIN STUDENT PROFILE STRENGTHENING PROJECT IN GRADE V OF MIS HIDAYATUL MUHAJIRIN, PALANGKA RAYA CITY - Siti Nur Hasanah; Sulistyowati; Nurul Hikmah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
By utilizing a qualitative descriptive approach based on interviews, observations, and documentation, this study attempts to narrate the implementation of the Pancasila and Rahmatan Lil Alamin Student Profile Strengthening Project Assessment in grade V at MIS Hidayatul Muhajirin, Palangka Raya City. The results show that the project implementation went well. The school formed a facilitator team to design, implement, and monitor activities with the support of the madrasah principal, teachers, and school community. The project was designed based on the needs of the madrasah with contextual themes such as processing plastic waste into handicrafts. The project module became a guideline for teachers in instilling the values ​​of the Pancasila and Rahmatan Lil Alamin Student Profile, such as mutual cooperation, independence, creativity, and environmental awareness. The assessment was carried out comprehensively through observation of the process, results, and attitudes of students with collaboration between teachers. This implementation succeeded in improving critical thinking skills, creativity, and students' awareness of the importance of protecting the environment.